Peran Keluarga dalam Mengoptimalkan Perkembangan Anak - Hanifah, Razita; Farida, Nur Aini (Az-Zakiy: Journal of Islamic Studies, 2023)
Family is the main factor in the process of growth and development of children. The family or parents play a role in ensuring that their children are healthy and safe, providing facilities and infrastructure to develop skills and character in social media and inculcating social and cultural values ​​as early as possible. Parents provide love, acceptance, appreciation, recognition, and direction or guidance to their children. The relationship between parents and children is very important in building trust in others and in oneself. It can also help with children’s social, emotional and cognitive development. Research shows that parent-child relationships are warm, open and communicative; have a reasonable age limit; and communicating why the child should not do something, will increase self-confidence and achievement in school and society. In addition, children are better protected from negative things such as depression and drug use.